(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
In this article, conclusions are presented based on the results of research on the use of multimedia technologies in teaching English to children based on an integrative approach. Strengthening language skills through the use of multimedia tools together with poems, songs, reading books, dramatization is extremely effective in increasing the vocabulary of preschool children in English. English language - music - rhythm - creative activity In order to develop the child’s ability to listen, understand and speak, and to increase the motivation to acquire the English language, the technology of using the multimedia educational resource "English is fun" has been highlighted within the framework of the research